Estudo do tratamento térmico de envelhecimento em patamar simples e duplo da liga UNS N09925 - Toledo, Breno Mussy Feres (Universidade Federal de São Carlos, 2023)
It is well known that several researches related to the development of renewable and alternative energy sources are currently in course. However, with the continuous increase on energy demand around the world, it is still necessary to explore other energy resources, mainly on oil and gas field, available in extremely aggressive environments such as the deep-sea water levels. In order to reach such natural reservoirs and extract its resources, new classes of nickel-based superalloys were developed, offering better combination of properties to handle the application in these aggressive environments with higher-pressure levels, avoiding equipment failure due to Hydrogen embrittlement and stress corrosion cracking. Particularly, the alloy UNS N09925 presents superior mechanical resistance when compared to other similar alloys and keeps its excellent corrosion resistance, which allows us to use it for larger dimension parts and component manufacturing, such as tubular systems, valves, hangers, shafts, and fasteners. This characteristic is related to its primary strengthening mechanism called precipitation hardening. This mechanism is related to the precipitation of γ′ − Ni3(Al, Ti) in the austenitic matrix of the alloy, which contributes to restrict dislocation movement. However, it is well known that deleterious phases such as sigma (σ) and eta (η) also can form during the material aging cycle. Therefore, it is of great importance to improve our knowledge about this heat treatment of the alloy UNS N09925. With such knowledge, it becomes possible to choose adequate aging temperatures and time parameters to optimize the heat treatment cycle, commonly performed in two steps, in order to maximize the alloy aging potential. As a result, one can expect an increase in the mechanical resistance of the alloy and reduced precipitation of unwanted deleterious phases in the austenitic matrix, avoiding loss of toughness, ductility and corrosion resistance.
Study of single step and double step aging heat treatments of the alloy UNS N09925
Keywords: Ligas de níquel; UNS N09925; Tratamento térmico; Envelhecimento; Duplo patamar; Precipitação de fases; Nickel alloys; Heat treatment; Aging; Double step; Phase precipitation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA